Legal Liability in E-Commerce Agreements through the Cash on Delivery Payment System - Gusti Yosi Andri; Ayih Sutarih; Vivi Aulia Syaharanti; Endang Sutrisno (Sekolah Pascasarjana Universitas Swadaya Gunung Jati, 2022)
The online sale and purchase agreement is in principle the same as the conventional sale and purchase agreement. The difference is only in the medium, where the seller and the buyer do not meet directly (face to face) and payment and delivery of goods is determined according to the agreement in the provisions of article 1458 of the Civil Code. The problem to be studied is the legal construction in online buying and selling with COD payments and the responsibilities of the parties involved in buying and selling online. The method used is a normative juridical research with qualitative descriptive analysis. The results of the study can be explained that the legal construction of online buying and selling made in an electronic contract through an electronic system is a manifestation of the agreement of the parties as formulated in Article 47 PP PSTE Number 82 of 2012. With the validity of the electronic contract, the provisions of Article 1338 of the Civil Code will apply where the agreement made is valid will bind the parties, so that rights and obligations arise where the seller is obliged to send the ordered goods and the buyer must pay the agreed price. Because it is done online, the delivery of goods requires the services of a third party, namely an expedition service. Thus there are three different responsibilities, namely the seller is responsible for the suitability of the goods that have been ordered, the buyer is responsible for payment for the goods, and the expedition is responsible for delivering the goods safely. so that rights and obligations arise where the seller is obliged to send the ordered goods and the buyer must pay the agreed price. Because it is done online, the delivery of goods requires the services of a third party, namely an expedition service. Thus there are three different responsibilities, namely the seller is responsible for the suitability of the goods that have been ordered, the buyer is responsible for payment for the goods, and the expedition is responsible for delivering the goods safely. so that rights and obligations arise where the seller is obliged to send the ordered goods and the buyer must pay the agreed price. Because it is done online, the delivery of goods requires the services of a third party, namely an expedition service. Thus there are three different responsibilities, namely the seller is responsible for the suitability of the goods that have been ordered, the buyer is responsible for payment for the goods, and the expedition is responsible for delivering the goods safely.